STUDY THE EFFECT OF YEAST EXTRACT AND CYTOKININ 2ip ON EMBRYOGENIC CALLUS GROWTH OF DATE PALM - Al-Abadi, Usama (Iraqi Journal of Science, 2024)
The effects of yeast extract on embryogenic callus growth of date palm cv. Ashkar were studied. Various concentrations of yeast extract were used ( 0 , 50 , 100 , 250 , 500 and 1000 ) mg/L with two concentrations of the cytokinin 2ip (0 , 1) mg/L. Results showed that the conc. 250 mg/L in the absence of the cytokinin 2ip gave maximum fresh weight and length of somatic embryos , but this was not significantly differed from the control in dry weight. The conc. 50 mg/L in the presence of the cytokinin 2ip gave the highest number of somatic embryos. In addition, it was observed a browning in embryogenic callus at high concentrations of yeast extract (500 and 1000)mg/L. Thus, it is possible to use the yeast extract for growth of the embryogenic callus, while it is preferred to use yeast extract and cytokinin 2ip together for induction of somatic embryos.